2012
DOI: 10.4236/ojn.2012.23025
|View full text |Cite
|
Sign up to set email alerts
|

The effect of music therapy on the level of anxiety in the patients undergoing coronary angiography

Abstract: The sedative effects of music on healthy and sick individuals are known for centuries. Nowadays, nursing has used the efficacy of music therapy in interventions. The aim of the study was to determine the effect of music, which the patients undergoing a coronary angiography for the first time listened to during the intraoperative period, on the level of anxiety in the patients. The study was conducted experimentally as a pretest/posttest control group design. Data collection form; state-trait anxiety inventory,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 12 publications
1
38
1
1
Order By: Relevance
“…Thus, appropriate training, reduction of psychological problems, increase in the patient's participation, and their adherence to medical prescriptions can also provide some information that can lead to the decrease of the patients' anxiety about the disease. (1) The other results of this study was a decrease in the level of anxiety in the experimental group compared to the control group after the educational intervention by the peers, which complies with the results of the researches performed by Varaee et al (17) , Chan et al (18) and Doğan et al, (19) emphasizing the fact that the use of peer group education and patient-centered educational interventions can cause a decrease in the patients' anxiety. The studies showed that providing the patients with angiography-related instructions through the health staff would reduce the anxiety caused by invasive procedures.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, appropriate training, reduction of psychological problems, increase in the patient's participation, and their adherence to medical prescriptions can also provide some information that can lead to the decrease of the patients' anxiety about the disease. (1) The other results of this study was a decrease in the level of anxiety in the experimental group compared to the control group after the educational intervention by the peers, which complies with the results of the researches performed by Varaee et al (17) , Chan et al (18) and Doğan et al, (19) emphasizing the fact that the use of peer group education and patient-centered educational interventions can cause a decrease in the patients' anxiety. The studies showed that providing the patients with angiography-related instructions through the health staff would reduce the anxiety caused by invasive procedures.…”
Section: Discussionsupporting
confidence: 91%
“…Nurses have a responsibility to establish a healing and calm environment for patients before invasive procedures (Weeks & Nilsson, ). Nurses should recognize patients' anxieties and provide interventions to lessen these anxieties (Doğan & Şenturan, ). For instance, therapeutic sounds, daylight, pleasant views, and room colours can lessen anxiety during clinical interventions (Altimier, ).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Several studies have confirmed the effectiveness of providing information about the angiography process in reducing patient anxiety. 8,9 However, further research is required to identify the most effective approach and time to prepare a patient and their family for the procedure. 10 The use of an appropriate educational technique-such as educational leaflets or peer-facilitated or video-based training-may be effective in reducing patient anxiety.…”
mentioning
confidence: 99%